Active and Inactive Leg Hemodynamics during Sequential Single-Leg Interval Cycling - Gordon, N.; Abbiss, C.; Ihsan, M.; Maiorana, Andrew; Peiffer, J. (Lippincott Williams & Wilkins, 2018)
Copyright © 2018 by the American College of Sports Medicine. Introduction Leg order during sequential single-leg cycling (i.e., exercising both legs independently within a single session) may affect local muscular responses potentially influencing adaptations. This study examined the cardiovascular and skeletal muscle hemodynamic responses during double-leg and sequential single-leg cycling. Methods Ten young healthy adults (28 ± 6 yr) completed six 1-min double-leg intervals interspersed with 1 min of passive recovery and, on a separate occasion, 12 (six with one leg followed by six with the other leg) 1-min single-leg intervals interspersed with 1 min of passive recovery. Oxygen consumption, heart rate, blood pressure, muscle oxygenation, muscle blood volume, and power output were measured throughout each session. Results Oxygen consumption, heart rate, and power output were not different between sets of single-leg intervals, but the average of both sets was lower than the double-leg intervals. Mean arterial pressure was higher during double-leg compared with sequential single-leg intervals (115 ± 9 vs 104 ± 9 mm Hg, P < 0.05) and higher during the initial compared with second set of single-leg intervals (108 ± 10 vs 101 ± 10 mm Hg, P < 0.05). The increase in muscle blood volume from baseline was similar between the active single leg and the double leg (267 ± 150 vs 214 ± 169 µM·cm, P = 0.26). The pattern of change in muscle blood volume from the initial to second set of intervals was significantly different (P < 0.05) when the leg was active in the initial (-52.3% ± 111.6%) compared with second set (65.1% ± 152.9%). Conclusions These data indicate that the order in which each leg performs sequential single-leg cycling influences the local hemodynamic responses, with the inactive muscle influencing the stimulus experienced by the contralateral leg.